Caracterización De La Pérdida Temprana De Implantes En Pacientes Sometidos A Procedimientos De Implantología En Un Postgrado De Periodoncia (2021)
Objective. To describe the sociodemographic, systemic, local, preoperative, intraoperative and postoperative conditions of patients undergoing implantology procedures by postgraduate periodontics from Antonio Nariño University from 2016 to 2021. Methodology. This retrospective and cross-sectional descriptive observational study was carried out by reviewing all the medical records of implant cases at Postgraduate Periodontics clinics. In order to measure the success or failure of these procedures, or the early failure of dental implants, an instrument was designed for this research project. An analysis was performed using descriptive statistics and a Chi square test. Results. 320 implants were evaluated in 150 patients. It was observed that 15 cases failed early. Conclusion. the failure rate was measured to be 4.7%. Furthermore, a strong relationship between bone loss and early implant failure was established.